Shoulder Muscles\' Function during Arm Flexion with and without Load in Patient\'s with Chronic Low Back Pain and Healthy Individuals - Nader Farahpour; Maryam Kamari; Amirali Jafarnezhadgero; Amirhosein Yazdani (Islamic Azad University, Hamedan Branch, 2016)
Objective: Shoulder muscle injuries are very prevalence. So determining of injuries mechanism could be a suitable way for identifying rehabilitation methods. The purpose of this study was to compare the electromygraphical activity of shoulder girdle muscles in lowback pain patients and healthy subjects during arm flexion with and without load. Methods: Tensubjects with chronic low back pain and ten age-matched control healthy subjects participated in this study. All participants were asked to perform arm flexion activities with and without load (with both dominant and nondominant sides) in a standing position. The outcome measures included electromygraphical activity of anterior and medial deltoid, infra and supra spinatus muscles for both groups. MANOVA and repeated measure statistical tests were used for between and within group comparisons. Alpha level was set at p˂0.05. Results:The intensity of muscle activity in anterior and medial deltoid, infra spinatus and supra spinatus muscles of dominant upper limb in healthy group were 26.3±2.67, 17.01±2.02, 11.1±1.67, 12.40±2.34 percent of maximum voluntary isometric cotraction, respectively. These values for patients group were 27.90±3.78, 14.73±3.14, 16.48±2.37, and 18.19±3.31, respectively. There were not any significant diffrences between groups (p˃0.05). Load effect in dominant upper limb for the groups accounted for 132% and 136% increase in the total muscular activity. Conclusion: Shoulder girdle muscle activity is similar in low back pain patients compred with the healthy subjects during arm flexion. It seems that low back pain didn't have any affect on shoulder muscular activiry; however, further studies are warranted.